Resilience oriented leadership in hospital management during COVID 19: a framework for hospital resilience and hypertension care continuity. - Pramono, Rudy; Wedhasari, Ni Putu Ayu Paramitha; Ginting, Leni Meipina (Revista Latinoamericana de Hipertensión, 2026)
Resilience-oriented leadership has emerged as a pivotal determinant of hospital performance during the COVID-19 pandemic. This qualitative meta-synthesis systematically integrates 12 studies conducted between 2020 and 2025 across diverse geographic regions, encompassing 1 372 hospital staff. By combining meta-ethnography and thematic synthesis, we identified six interrelated dimensions that constitute a comprehensive resilience framework: trust-based and empathetic leadership; adaptive and transformational leadership; psychological safety and well-being support; systemic and shared governance; digital adaptation and data-driven policy implementation; and human-resource support and culture. Each dimension is illustrated with direct participant quotations and corroborated across multiple contexts, demonstrating both universality and context-specific nuances. The trust-based dimension emphasizes visible presence and transparent communication; adaptive leadership facilitates rapid protocol adjustments; psychological safety mitigates burnout; shared governance ensures coordinated decision-making; digital adaptation accelerates information flow; and robust human-resource practices sustain workforce capacity. Collectively, these components operate across individual, relational, and structural levels, enabling hospitals to maintain operational continuity and sustain chronic disease care, notably hypertension management, amid crisis. The findings underscore that resilience is not a single attribute but a dynamic interplay of emotional, structural, and technological capabilities. Implications for practice include designing leadership training that fosters empathy, encouraging distributed decision-making, investing in digital infrastructure, and prioritizing staff well-being.